Systematic review of Marine Protected Area management effectiveness evaluation methods - Jean-Aimé Zafimahatradraibe; Lala NJ Ranaivomanana; Gildas GB Todinanahary; Houssoyni H. Madi; Tahiry Randrianjafimanana; Rodolphe Devillers; Arthur O. Tuda; Pascale Chabanet (Marine Policy, 2026)

Conservation ready marine spatial planning - Julie M. Reimer; Rodolphe Devillers; Brice Trouillet; Natalie C. Ban; Tundi Agardy; Joachim Claudet (Marine Policy, 2023)

SAR Satellite Imagery Reveals the Impact of the Covid-19 Crisis on Ship Frequentation in the French Mediterranean Waters - Ignacio Pita; Raphael Seguin; Yunne-Jai Shin; Pauline Viguier; Thibault Catry; Rodolphe Devillers; David Mouillot (Frontiers in Marine Science, 2022)
The Covid-19 pandemic is the latest example in a growing number of health, social, economic, and environmental crises humanity is facing. The multiple consequences of this pandemic crisis required strong responses from governments, including strict lockdowns. Yet, the impact of lockdowns on coastal ecosystems and maritime activities is still challenging to quantify over large spatial scales in comparison to the pre-Covid period. In this study, we used an object detection algorithm on Synthetic Aperture Radar (SAR) images acquired by the two Sentinel-1 satellites to assess the impact of the Covid-19 crisis on the presence of boats before, during and after lockdown periods in the French Mediterranean Exclusive Economic Zone. During the French most severe lockdown period (March – May 2020), we observed that ship frequentation remained at the same level from March to July 2020, instead of rising towards the summer peak like in previous years. Then, ship frequentation increased rapidly to a normal level in August 2020 when restrictions were lifted. By comparing morning and evening (7:00 am and 7:00 pm) ship frequentation during this period to pre-Covid years, we observed contrasting patterns. On the one hand, morning detections were particularly high, while on the other hand evening detections were significantly lower and less concentrated in coastal touristic waters than in previous years. Overall, we found a 9% decrease in ship frequentation between the year 2020 and the 2017-2019 period, with a maximum of 43% drop in June 2020 due to the lockdown. So, the Covid -19 crisis induced only a very short-term reduction in maritime activities but did not markedly reduce the annual ship frequentation in the French Mediterranean waters. The satellite imagery approach is an alternative method that improves our understanding of the pandemic impacts at an unprecedented spatiotemporal scale and resolution.

Bridging theory and practice in ecosystem services mapping: a systematic review - Rachel E. Bitoun; Ewan Trégarot; Rodolphe Devillers (Environment Systems and Decisions, 2022)
The mapping and assessment of Ecosystem Services (ES) aims at better connecting environmental conservation, economic development, and human well-being. However, 60 years after the development of the ES concept, a persistent gap remains between the production of scientific knowledge on ES and its use in support of policy and management. Here, we report on a systematic review of the scientific literature that helps better understand key challenges and offers potential solutions to bridge this gap. The review considered four criteria: (1) how stakeholders participate to studies; (2) how usable ES maps are for decision-making; (3) what policy recommendations were made; and (4) what research recommendations were made. The analysis of 135 papers published between 2008 and 2020 revealed diverse technical and conceptual challenges that could prevent the effective use of ES concepts and methods outside the academic realm. The main challenges identified in the literature were the uncertainty levels of ES mapping outputs, issues of spatial scales, the understanding of ES interactions, and the need for temporal analysis. Many policies rely on mapped outcomes, creating a window of opportunity for the uptake of ES mapping into policy-making. However, it remains key to involve stakeholders early in the co-design of ES studies and to better understand their preferences and motivation to adopt ES mapping in their practices. The study shows that higher levels of learnability of ES mapping practices, further popularization to foster public awareness, and increased capacity building would facilitate the ES concept uptake into decision and policy-making.

Seafloor mapping to support conservation planning in an ecologically unique fjord in Newfoundland and Labrador, Canada - Beatrice Proudfoot; Rodolphe Devillers; Craig J. Brown; Evan Edinger; Alison Copeland (Journal of Coastal Conservation, 2020)

How fisher‐influenced marine closed areas contribute to ecosystem‐based management: A review and performance indicator scorecard - Kate Kincaid; George Rose; Rodolphe Devillers (Fish and Fisheries, 2017)
A rapid review of the literature on closed areas that recognize key ecosystem‐based management ( EBM ) principles of fisheries and biodiversity conservation and had fisher involvement was employed to review closed areas worldwide from a fisheries perspective and to develop a scorecard that can assess their efficacy. The review provided 523 abstracts of which 19 areas from various regions worldwide had peer‐reviewed studies that met strict selection criteria. Criteria included fisher involvement, biodiversity conservation and fisheries management objectives. A repeat search without “fisher” and synonyms found, 62,622 papers indicating that most closed area studies had no mention of any fisher involvement. The general success of the areas selected suggests that fisher involvement benefits both biological conservation and fisheries management. Fisheries and biodiversity conservation outcomes were not exclusive to any one type of management closure (e.g. MPA , Fishery Closure). Twenty‐four indicators were selected, designed to provide measurable targets. High scoring indicators included management, planning and socio‐economic indicators such as local support (100%), habitat protection (100%), conservation and fisheries objectives (100%), monitoring (91.7%) and fishers concerns (91.7%). Bio‐ecological‐based indicators scored lower in most cases for all types of areas. Fisheries closures rated as highly as the MPA s with respect to both fisheries and bio‐ecological indicators. The scorecard provided a reasonable means to evaluate management success in the light of often qualitative or missing data. Addressing the interests and utilizing knowledge of those affected by closures and familiar with the area, most often local fishers, is key to achieving management objectives.

Incentivizing More Effective Marine Protected Areas with the Global Ocean Refuge System (GLORES) - Sarah O. Hameed; Leslie A. Cornick; Rodolphe Devillers; Lance E. Morgan (Frontiers in Marine Science, 2017)

Limited Contribution of Small Marine Protected Areas to Regional Biodiversity: The Example of a Small Canadian No-Take MPA - Emilie Novaczek; Victoria Howse; Christina Pretty; Rodolphe Devillers; Evan Edinger; Alison Copeland (Frontiers in Marine Science, 2017)

Preface - Rodolphe Devillers; Rosaline Canessa; Dawn Wright (Marine Geodesy, 2014)

From Movement Data to Objects Behavior Using Semantic Trajectory and Semantic Events - Arnaud Vandecasteele; Rodolphe Devillers; Aldo Napoli (Marine Geodesy, 2014)

Marine habitat mapping in support of Marine Protected Area management in a subarctic fjord: Gilbert Bay, Labrador, Canada - Alison Copeland; Evan Edinger; Rodolphe Devillers; Trevor Bell; Philippe LeBlanc; Joe Wroblewski (Journal of Coastal Conservation, 2013)

Comparing interactive and automated mapping systems for supporting fisheries enforcement activities—a case study on vessel monitoring systems (VMS) - René A. Enguehard; Rodolphe Devillers; Orland Hoeber (Journal of Coastal Conservation, 2013)